(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Indian Women’s Movement can claim to be a hundred years old as of now. During a span of a century several changes have taken place within it. Apart from several ups and downs the movement also saw an expansion in its scope, a variation in the themes and issues tackled by it and a definite broadening of its base over the years to include the women from all the spectrums of society. Feminism in colonial India was essentially entwined with the issue of nationalism – an idea that was the driving force of anti- colonial movements not only in India but other countries grappling with the juggernaut of colonialism. The feminist movements of some of the other countries in the world are much older in terms of being organized efforts at reform. The attempt here is to define what a ‘movement’ is and how it emerges and then merges to attain a larger connotation of the ‘movement’.The other emphasis in this paper is on the historiographical and ideological evolution that has taken place in the writings on these movements both by indigenous as well as international scholars. There is no dearth of writing and the enormous amount of literature present makes the task of writing on women’s movement extremely demanding. This paper tries to analyze, although rather briefly, the various aspects related to the women’s movement viz. its varied achievements over the century on the issues concerning women. As the story unfolds one gets an impression of a movement that underwent several changes over the years not only in terms of its nature but also in terms of the ideological trends involved namely, revivalist, reformist, nationalist, imperialist influence before independence liberal, Marxist and socialist during both the phases i.e. pre and post-independence period and post- colonialists and post - modernist in the contemporary context.Women’s movement forms a part of the larger social movements which are understood by sociologists as a type of group action undertaken by large groups of individuals or organizations focused on specific political or social issues. This is a key word used by the political scientists and sociologists to describe the mobility of the newly emergent forces prodded on by the 19th century forces of industrialization and urbanization. They have developed a variety of theories and empirical research on social movements which argue that the freedom of expression, education and economic independence, considered as the hallmarks of Western culture are responsible for the variety and flagrancy of the social movements.